2020
DOI: 10.3390/molecules25225414
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Activities and Nanomedicine Delivery Strategies for Brucea javanica Oil and Its Molecular Components

Abstract: Brucea javanica oil (BJO) is widely used in traditional Chinese medicine to treat various types of cancer and inflammatory diseases. There is significant interest in understanding the medicinal activities of BJO and its molecular components, especially quassinoids, and in exploring how they can be incorporated into nanomedicine delivery strategies for improved application prospects. Herein, we cover the latest progress in developing different classes of drug delivery vehicles, including nanoemulsions, liposome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…However, BJOE has a multidirectional dynamic unstable dispersion system; an improper temperature can cause separation. its preparation is complex, and its effective components are poorly soluble in fat, leading to low bioavailability in clinical application ( Yang et al, 2014 ; Yoon et al, 2020 ). Therefore, studies exploring more effective, stable and efficient dosage forms are needed.…”
Section: Chinese Patent Medicines In Primary Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, BJOE has a multidirectional dynamic unstable dispersion system; an improper temperature can cause separation. its preparation is complex, and its effective components are poorly soluble in fat, leading to low bioavailability in clinical application ( Yang et al, 2014 ; Yoon et al, 2020 ). Therefore, studies exploring more effective, stable and efficient dosage forms are needed.…”
Section: Chinese Patent Medicines In Primary Liver Cancermentioning
confidence: 99%
“…Therefore, studies exploring more effective, stable and efficient dosage forms are needed. New dosage forms of BJO include gastroretentive floating bead, self-microemulsion, nanoemulsion, liposomes, nanostructured lipid carriers, and sponges ( Yoon et al, 2020 ).…”
Section: Chinese Patent Medicines In Primary Liver Cancermentioning
confidence: 99%
“…Brucea javanica oil emulsion injection (BJOEI) is a Chinese patent medicine extracted from Brucea javanica ( Yadanzi in Chinese Pinyin ). Its main active component is quassinoid sand fatty acids, which exert anticancer effects through multiple mechanisms ( 12 ). Studies have shown the synergistic effects of BJOEI combined with chemoradiotherapy on tumor attenuation, such as reversal of chemotherapy resistance, reduction of the recurrence and metastasis rates, and improvement of the quality of life ( 13 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brucea javanica oil emulsion injection (BJOEI) is a new generation of antitumour drugs extracted from the traditional Chinese medicine Brucea javanica, mainly including quassinoids and fatty acids. Its main active components are oleic and linoleic acids [28]. Studies have found that BJOE exerts its antitumour effects primarily by inhibiting cell proliferation [29], inducing apoptosis [30], and interfering with cell cycle and energy metabolism [31] and has been widely used in the treatment of a variety of tumour-related diseases [32,33].…”
Section: Introductionmentioning
confidence: 99%